Bilateral Supracondylar Humerus Fracture in Pediatric after a Fall on an Outstretched Hand - Basam Alanazi; Jameel Fakeeha; Abdulrahman Pasha; Hussam Alqulaiti; Hani Alharbi; Jameel Mahmoud (Case Reports in Orthopedics)
Background. Supracondylar humerus fracture (SCH) is common in the pediatric age group 5-7 years, mostly due to a fall on an outstretched hand. However, a bilateral SCH is rarely observed in this age group. Management of SCH is either surgical or conservative based on the following factors: patient age, fracture pattern and neurovascular involvement. Complications of a displaced SCH can be dramatically reduced by early surgical fixation. Acute complications include: neurovascular injury and compartment syndrome, and long term complications include: stiffness, infections and angular deformities. In this article, we present a rare case of bilateral supracondylar humerus fractures with a six-months follow-up.